Testing the Recommendations of the Washington State Nutrition and Physical Activity Plan: The Moses Lake Case Study - Donna B. Johnson, PhD, RD; Lynne T. Smith, PhD, MPH, RD (Centers for Disease Control and Prevention, 2006)
Background The Washington State Nutrition and Physical Activity Plan provides a framework in which policy makers can work together to build and support healthy environments for nutrition and physical activity. The city of Moses Lake, Wash, was chosen to serve as a pilot site to test the conceptual approaches and recommendations of the plan and to develop a model for healthy communities elsewhere in the state. Context Moses Lake is an ethnically diverse, geographically isolated town with a population of about 15,000. Methods An advisory committee used data from an inventory of local policies and environments, along with the recommendations from the state plan, to develop a plan for Healthy Communities Moses Lake. Three initiatives were chosen for the first actions: a connected system of trails and paths, enhanced facilities for breastfeeding in the community, and a community garden. Consequences Records of cumulative actions demonstrated that Healthy Communities Moses Lake continued to be an active and productive project. Initial measures of success were collected by each of the three first action teams. Environmental changes will be monitored by comparison with the initial inventory of local policies. Long-term health outcomes in Moses Lake will be monitored by the Washington State Department of Health.